Antibiotic resistance in Helicobacter pylori: a genetic and physiological perspective - Rania G. Elbaiomy; Xiaoling Luo; Rong Guo; Shiyuan Deng; Meifang Du; Ahmed H. El-Sappah; Mohammed Bakeer; Mahmoud M. Azzam; Ahmed A. Elolimy; Mahmoud Madkour; Zaixin Li; Zhi Zhang (Gut Pathogens)
Abstract The identification of Helicobacter pylori (H. pylori) infection as the primary etiology of gastroduodenal diseases represents a significant advancement in the field of gastroenterology. The management of these diseases has undergone a substantial transformation, and antibiotic treatment is now universally applicable. H. pylori has been the subject of numerous investigations to determine the prevalence of antibiotic resistance. However, many of these studies are limited, particularly regarding the number and representativeness of the strains assessed. Genetic and physiological modifications, such as gene mutations, efflux pump alterations, biofilm formation, and coccoid formation, contribute to the observed resistance. Our review focuses on the emergence of antibiotic-resistant strains, particularly emphasizing the various modifications of H. pylori that confer this resistance. In conclusion, we elucidate the challenges, potential solutions, and prospects in this field, providing researchers with the knowledge necessary to overcome the resistance exhibited by H. pylori.